2021
DOI: 10.3389/fclim.2020.589282
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Climate Information for Decision-Making in Africa: Contrasting User-Centered and Knowledge-Centered Approaches

Abstract: This study examined ways in which climate information was mobilized for use under Future Climate for Africa (FCFA), an applied research program to improve the use of climate information to support medium-term (5–40 years) policies and planning in sub-Saharan Africa. Past research has underscored the interdependent relationship between user engagement and knowledge mobilization in effective climate knowledge uptake. The study used a document analysis of 46 program ou tputs and semi-structured interviews with 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…The engagement of policymakers and decision-makers in the co-production of gender analyses (particularly from the policy arena) resulted in policy briefs that identified gender-related gaps and informed the actions to be undertaken (Masiko et al, 2019;Chingarande et al, 2020;such publications include AGNES, 2020). Those policy briefs then served as leverage points through which to further advance collaborations, similar to a finding of Harvey et al (2021) which identified policy briefs as boundary objects through which the spheres of decisionmaking and science could be linked.…”
Section: Identifying Leverage Points Through Science and Co-productio...mentioning
confidence: 76%
“…The engagement of policymakers and decision-makers in the co-production of gender analyses (particularly from the policy arena) resulted in policy briefs that identified gender-related gaps and informed the actions to be undertaken (Masiko et al, 2019;Chingarande et al, 2020;such publications include AGNES, 2020). Those policy briefs then served as leverage points through which to further advance collaborations, similar to a finding of Harvey et al (2021) which identified policy briefs as boundary objects through which the spheres of decisionmaking and science could be linked.…”
Section: Identifying Leverage Points Through Science and Co-productio...mentioning
confidence: 76%
“…However, this is still not at scale that is sufficient to address the critical role of medium to long-term projections in long-term planning, particularly for local decision makers (Jones et al, 2015). Most existing efforts for advancing MLT CIS are targeted towards increasing access for and use by national and international planners (Harvey et al, 2021;Sultan et al, 2020) to inform long-term development planning and risk management and to avoid maladaptation (Payo et al, 2016). Some other CIS efforts, for example, FRACTAL target sub-national decision makers such as city governments (FRACTAL, n.d.;Janes et al, 2020) Assessments attribute the limited development and use of MLT in CIS to three drivers.…”
Section: Country/ Regionmentioning
confidence: 99%
“…Influences related to information and knowledge that must be taken into account include the power and status of those generating the knowledge (Fazey 2012), what information is available, access, and capacity for discernment. Other important aspects include how the information is presented, learning style, information absorptive capacity, willingness to query the information provided, level of information processing, the interplay between user engagement and knowledge mobilisation (Harvey et al 2021) and degree of confirmation bias and distraction level (Gorman and Gorman 2017;Ariely 2010). Hitziger et al (2019) developed a tool for evaluating multi-stakeholder initiatives at the science-policy interface with an emphasis on transformation and systems knowledge.…”
Section: Theoretical Underpinning Of Case Applicationmentioning
confidence: 99%